The doctoral thesis citation in biology and linguistics - Gallardo, Susana (Íkala, Revista de Lenguaje y Cultura, 2010)
The objective was to determine differences in the use of disciplinary citation in doctoral theses. In this sense, using a qualitative approach we analyzed the form and functions of citations in two sections ("Introduction" and "Conclusions") of doctoral theses of biology and linguistics. On the one hand, we have explored the lexis and grammar so as to determine the form of citations in different rhetorical moves. On the other hand, from a pragmatic point of view we have determined the place of the referred content in the illocutionary structure. Therefore we observed a correlation between the form of citations and function of segment or movement in which they appear. In the discussion section of a biology thesis, citation played the role of enablement or justification of claims. These results suggest that authors in biology need to support their conclusions with evidence from other investigations. In our opinion, the differences between disciplines are related with different epistemological conceptions. Recieved: 28-12-09 / Accepted: 13-04-2010 How to reference this article: Gallardo, S. (2010). La citación en tesis doctorales de biología y lingüística. Íkala, 15(3), 153 – 177.